2013
DOI: 10.1017/s0022215113002478
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing outcomes following surgical and non-surgical treatment for advanced laryngeal cancer

Abstract: Long-term dysphagia is a common outcome of treatment for advanced laryngeal cancer. Patients treated with chemoradiotherapy and laryngectomy reported the worst overall outcomes. More longitudinal prospective research with large treatment groups is needed to investigate swallowing outcomes following different treatment methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 30 publications
2
36
0
1
Order By: Relevance
“…20,21 A comparison of functional outcomes from previous studies is difficult because the assessment measures were not standardized. 18,19,32,33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 A comparison of functional outcomes from previous studies is difficult because the assessment measures were not standardized. 18,19,32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Gastrostomy dependence indicated significant swallowing dysfunction that required supplementation through a gastrostomy tube. Tracheostomy tube dependence was higher among patients receiving CRT, which may reflect more severe tissue damage caused by adding CT. Two independent studies 32,33 found that patients with advanced laryngeal cancer receiving RT or surgery had minimal swallowing problems; however, they had worse swallowing outcomes if they received CRT and CRT plus surgery.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,8,9,11 Although highest in the treatment and early follow-up phase, 2,8-10 supportive care needs may remain through the long-term follow-up. [14][15][16] In addition, they have often been treated with (chemo)radiation and/or neck dissection, which may induce problems, such as dysphagia and shoulder complaints. These patients encounter several adjustments in normal daily functioning, which they have to live with for the rest of their lives, including adjustments in airway management, smell, swallowing, and speech.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who received primary radiochemotherapy for organ preservation have significantly higher dysphagia rates compared to laryngectomees [142], [149]. Furthermore, patients after total laryngectomy alone have better swallowing function than patients after total laryngectomy and adjuvant radiation or salvage laryngectomy [145], [153], [154]. …”
Section: Therapy Of Primarily Diagnosed Laryngeal Cancermentioning
confidence: 99%